PENGARUH PENERAPAN CORPORATE GOVERNANCE TERHADAP TIMBULNYA EARNINGS MANAGEMENT DALAM MENILAI KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN DI INDONESIA - YUSRIATI NUR FARIDA; YULI PRASETYO; ELIADA HERWIYANTI (Jurnal Bisnis dan Akuntansi, 2010)
The study examined the influence of corporate governance imple-mentations (consist of the amount of commissioner board, existence of audit committee, board of independent commissioner, managerial ownership and institutional ownership) towards earnings management to evaluate company operations among listed of banking industries in Indonesia Stock Exchange which published their annual reports from 2005 until 2007. The analysis method of this research used multiple regressions. The results of this study showed that (1) corporate governance implementations (consist of the amount of commissioner board, existence of audit committee, board of independent commissioner, managerial ownership and institutional ownership) toward earnings management of banking industries in Indonesia had significant influence for managerial ownership proxy; (2) Earnings management act had not significant influence toward financial performance of banking industries in Indonesia; (3) Relationship between corporate governance implement-tations (consist of the amount of commissioner board, existence of audit committee, board of independent commissioner, managerial ownership and institutional ownership) toward financial performance was mediated by earnings management of banking industries in Indonesia had not significant